An operational effectiveness analysis of legacy and future mine countermeasures systems using discrete event simulation. (April 2020) - Beery, Paul; Byram, Timothy; Gatley, Eric; Giammarco, Kristin; Williams, Richard; Paulo, Eugene
This paper conducts an operational analysis of legacy and future mine warfare systems using discrete event simulation. The research focuses on a comparative analysis of the MCM-1 Avenger ship, supported by the MH-53E helicopter, and the Littoral Combat Ship, supported by external unmanned systems, in active, defense mine countermeasures operations. The paper develops architectural representations of the functional activities associated with mine countermeasures operations, as well as architectural representations of past, current, and potential future physical entities involved in minehunting and mine neutralization. Those architectural representations are used as the basis for the development of two distinct discrete event simulation models, one corresponding to legacy (MCM-1 Avenger) operations and another corresponding to future (Littoral Combat Ship) operations. The results of the simulation are analyzed using statistical regression. The regression results indicate that the key performance drivers for both the legacy and future systems show considerable overlap, and also suggest that the legacy assets meet or exceed the performance of future assets in several measures of effectiveness. The simulation model for the future assets is reconsidered to develop recommendations regarding alterations to the future force that enable the future force to exceed the operational performance of the legacy force.